Autochthonous Red Varieties in the Oltrepò Pavese Wine District: An Effective Tool for Adaptation to Climate Change - Alberto Vercesi; Matteo Gatti; Alessandra Garavani; Francesco Pelusi; Stefano Poni (Horticulturae, 2024)
Global warming is challenging the performances of medium-to-late ripening red Vitis vinifera cultivars whose harvest dates might be consistently anticipated at the detriment of still insufficient phenolic maturity. A 3-year study (2021–2023) was devised to compare cv Croatina—the most grown red cultivar in the Oltrepò Pavese district—with the following five autochthonous genotypes: Croà, Moradella, Mornasca, Ughetta, and Uva Rara. Weather trends, main yield components, and grape composition parameters were recorded each year; in two out of the three trial seasons, ripening curves for total soluble solids (TSS) and titratable acidity (TA) were also derived. In terms of yield performance, all minor varieties showed a level of basal node fruitfulness (about 1.1 clusters/shoot) high enough to perform short pruning, which was not possible to achieve in Croatina. As per grape quality at harvest, Uva Rara behaved quite similarly to Croatina, whereas Ughetta, Moradella, and Croà were judged to be unsuitable due to poor berry coloration at harvest (less than 0.7 mg/kg). Conversely, Mornasca’s performance was truly interesting and promising. In 2021 and 2023, Mornasca had delayed sugar accumulation, which was strongly uncoupled with total anthocyanins, which were not limited. In 2022, a hot and dry season, Mornasca outdid Croatina because the required TSS was assured, and the color significantly improved. The conclusion is that Mornasca is less susceptible than Croatina to imbalances in pigment formation or degradation, which typically occurs with berry overheating.